Оцінка критичних сценаріїв щодо надходження інвестицій в розвиток об’єктів електроенергетики України - Nechaieva T.P. (General Energy Institute of the National Academy of Sciences of Ukraine, 2017)
We analyze the existing plans and programs for the development of generating capacities of the Ukrainian UPS and, on this basis, form the variants of prospects of their implementation depending on the amount of financing. Scenario calculations of the prospective structure of generating capacities of the Ukrainian UPS and the characteristics of its operation have shown that improper investments in the development of generating capacities can lead to the collapse of the Ukrainian power system already after 2030, when the large-scale decommissioning of existing capacities will begin even despite their life extention. For sustainable, environmentally acceptable operation of the energy system, it is necessary to solve the problem of finding sources of investment in the industry in the near future, especially for the implementation of high-capital intensive and large-scale projects with a long period of implementation, such as the construction of new nuclear  and pumped storage power plants.